1999
DOI: 10.1097/00001756-199902250-00038
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cation selectivity of the subtypes of low voltage-activated Ca2+ channels in thalamic neurons

Abstract: LVA Ca2+ current in isolated associative neurons from the laterodorsal thalamic nucleus of 14- to 17-day-old rats was dissected into two, 'fast' and 'slow', components based on the difference in the kinetics of inactivation. The selectivity of the channel responsible for the fast LVA current for Ca2+, Sr2+ and Ba2+ (I(Ca):I(Sr):I(Ba) = 1.0:1.23:0.94) as well as the shifts of the I-V produced by these ions were found to be almost identical to those observed for LVA channels in other preparations. The channel re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
12
1
1
Order By: Relevance
“…According to the expression profile of ␣ 1I and ␣ 1G mRNA in rat brain (23), it was suggested that ␣ 1I and ␣ 1G currents could coexist in thalamic structures. Indeed, it was reported that the LVA current in rat thalamic reticular and laterodorsal neurons could be separated into fast and slow components (16,24,25). By contrast, our Northern and dot blot data have not confirmed that human thalamic structures expressed the ␣ 1I mRNA at high level.…”
Section: Characterization Of Human ␣ 1i T-type Ca 2ϩ Channelscontrasting
confidence: 85%
“…According to the expression profile of ␣ 1I and ␣ 1G mRNA in rat brain (23), it was suggested that ␣ 1I and ␣ 1G currents could coexist in thalamic structures. Indeed, it was reported that the LVA current in rat thalamic reticular and laterodorsal neurons could be separated into fast and slow components (16,24,25). By contrast, our Northern and dot blot data have not confirmed that human thalamic structures expressed the ␣ 1I mRNA at high level.…”
Section: Characterization Of Human ␣ 1i T-type Ca 2ϩ Channelscontrasting
confidence: 85%
“…None of these agents were absolutely specific for either channel subtype, although nifedipine, flunarizine and La 3 had a distinct preference for the fast channel while the slow one was more sensitive to Ni 2+ . This pharmacology of the fast channel, together with its typical T-type selectivity [20] and large whole-cell current, suggests that this subtype is a representative of the major population of LVA Ca 2+ channels in the central nervous system. Although apparently Ni 2+ sensitive, the slow channel's quite unusual selectivity [20] does not permit its classification simply as the peripheral type.…”
Section: Amplitudes and Densities Of Lva Ca 2+ Currentsmentioning
confidence: 92%
“…In our previous study [20] we used the exponential stripping procedure illustrated in Fig. 1A, B to dissect the overall LVA current into fast and slow components corresponding to the activation of the two subtypes of LVA channels.…”
Section: Kinetic Dissection Of the Currentsmentioning
confidence: 99%
See 2 more Smart Citations